Plasenta Previa Sebagai Faktor Protektif Kejadian Preeklamsia Pada Ibu Hamil - Nadila Ayuni Putri (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Background Placenta previa is partial or complete closure of the cervix by the placenta. The incidence of placenta previa is significantly related to the presence of uterine and endometrial injuries such as curettage, previous placenta previa events and cesarean scar. Gestational hypertension and preeclampsia are the most common complications that occur in pregnancy. The incidence reaches 6-8%. Preeclampsia increases the risk of adverse fetuses, such as preterm birth, intrauterine growth restriction, fetal death and antepartum hemorrhage.Content: Some research states that the incidence of placenta previa in pregnant women is a protective factor for the occurrence of preeclampsia. This can occur through a good mechanism of trophoblast invasion in pregnant women with placenta previa, where the trophoblast attaches deeper than its normal attachment and attachment site which is rich in oxygen, so that fetomaternal blood flow becomes good. Conclusion: There are protective factors present in patients with placenta previa thereby reducing the incidence of preeclampsia.